Prevention and Reversal of Antibody Responses Against Factor IX in Gene Therapy for Hemophilia B - Nayak, Sushrusha; Sarkar, Debalina; Perrin, George Q.; Moghimi, Babak; Hoffman, Brad E.; Zhou, Shangzhen; Byrne, Barry J.; Herzog, Roland W. (Frontiers in Microbiology, 2011)
Intramuscular (IM) administration of an adeno-associated viral (AAV) vector represents a simple and safe method of gene transfer for treatment of the X-linked bleeding disorder hemophilia B (factor IX, F.IX, deficiency). However, the approach is hampered by an increased risk of immune responses against F.IX. Previously, we demonstrated that the drug cocktail of immune suppressants rapamycin, IL-10, and a specific peptide (encoding a dominant CD4+ T cell epitope) caused an induction of regulatory T cells (Treg) with a concomitant apoptosis of antigen-specific effector T cells (J. Thromb. Haemost. 7:1523, 2009). This protocol was effective in preventing inhibitory antibody formation against human F.IX (hF.IX) in muscle gene transfer to C3H/HeJ hemophilia B mice (with targeted F9 gene deletion). Here, we show that this protocol can also be used to reverse inhibitor formation. IM injection of AAV1-hF.IX vector resulted in inhibitors of on average 8-10 BU within 1 month. Subsequent treatment with the tolerogenic cocktail accomplished a rapid reduction of hF.IX-specific antibodies to <2 BU, which lasted for >4.5 months. Systemic hF.IX expression increased from undetectable to >200 ng/ml, and coagulation times improved. In addition, we developed an alternative prophylactic protocol against inhibitor formation that did not require knowledge of T cell epitopes, consisting of daily oral administration of rapamycin for 1-month combined with frequent, low-dose intravenous injection of hF.IX protein. Experiments in T cell receptor transgenic mice showed that the route and dosing schedule of drug administration substantially affected Treg induction. When combined with intravenous antigen administration, oral delivery of rapamycin had to be performed daily in order to induce Treg, which were suppressive and phenotypically comparable to natural Treg.